Studies on Schismatoglottideae (Araceae) of Borneo XXXIX: Schismatoglottis persistens, a new rhizomatous rheophytic species for the Schismatoglottis Multiflora Group - Wong, Sin Yeng; Boyce, P.C (BGBM Berlin-Dahlem., 2014)
During fieldwork at Batang Ai, SW Sarawak, in 2004 we encountered a rheophytic rhizomatous Phymatarum-like aroid growing on shaded consolidated alluvial clay-loam banks roughly along the upper spate zone of the Sungai Pedali, a steep-banked forest stream draining into the larger Sungai Sumpa. Despite extensive searching over several days we failed to find the plant in flower; indeed we did not encounter any further populations. A living portion (collected as AR-2383) was brought into cultivation under permit and although growing well for several years it failed to flower until exposed to more light, more than in the heavily shaded conditions in which it grew in the wild. Flowering has revealed it not to belong to Phymatarum M. Hotta but instead to be a novel species of Schismatoglottis Zoll. & Moritzi remarkable in possessing an extensive epigeal, rooting rhizome from which tufts of erect leaves arise, the petioles of which have the petiolar sheath extended into a pair of long, free, persistent ligules, with the entire plant highly reminiscent of Phymatarum.